Inheritance Rights of Children Born in Mixed Marriages Reviewed from the Civil Code and Balinese Customary Law - Ni Putu Sayuri Dewi; M. Sofyan Pulungan; Meliyana Yustikarini (Dinasti Research, 2025)
This research is motivated by the existence of several legal systems in Indonesia that exist and develop in its diverse society, so that the inheritance rights of children born in mixed marriages should be obtained by examining not only through civil law in Indonesia, but also through customary law. This research was conducted to analyze how the inheritance rights of children born in mixed marriages are reviewed from the Civil Code and Balinese Customary Law. This paper was compiled using a doctrinal research method. The results of the study show that the inheritance rights in the Civil Code and Balinese Customary Law are both carried out by the testator who gives inheritance to the heirs solely to improve the welfare of the heirs. Although in Civil Law and Balinese Customary Law both want the best for their heirs, there are differences in the implementation of the distribution of the inheritance. This comparison can be seen from the differences in when the distribution of inheritance can be carried out, the differences in the elements of inheritance, the differences in objectives, and the differences in the parts of rights and obligations inherited by the heirs